DAMAGE PREDICTIONS IN CONCRETE SILO USING FINITE ‎ELEMENT ANALYSES - Sihem Kermiche; A. Haddi; C. Djelal (Fib Symposium 2016 Cape Town, South Africa, 2016)
The objective of this study is to improve the ultimate internal pressure capacity, the strength, and ‎durability of silos. The first part of this paper is to analyse the mechanical behaviour of reinforced ‎concrete silos during filling using numerical simulation approach. These results are compared with ‎results from analytical approach. The second part of this work concerns the reinforcement of silos ‎by external wrapping of damaged sections using carbon fibre reinforced polymer (CFRP) materials ‎as an alternative repair of the structure. The wheat is modelled by 8 solid elements, the reinforced ‎concrete silos are modelled by shell elements and their nonlinear behaviour is considered by ‎concrete damaged plasticity model. At the silo wall -wheat material interface, the friction is ‎modelled by Coulomb’s law and it is chosen in the range of 0.4 – 0.5. The results show that the use ‎of carbon fibre reinforced polymer materials offers a substantial benefit over the damage resistance ‎during filling silos‎
B.Redjel
O. Boussaid